Vitamin B 12 deficiency….The predominant cause of macrocytic anemia in pediatric population visiting Children hospital Lahore - Tooba Fateen, Zertaj Kashif, Sehar Shamshad Ali, Fauzia Aamer, Kanwar Sajid Ali, Muhammad Bilal Pasha, Sonia Zafar Warriach (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The purpose of this scrutiny was to note the part played by folic acid and vitamin B 12 inadequacies resulting in macrocytic anemia in pediatric community visiting our institute. Study Design: Retrospective cross sectional study Place and duration: Department of Hematology and Transfusion Medicine, The Children Hospital, University of Child Health Sciences, Lahore from Jan 2021 to Dec 2021. Methodology: Medical data of 294 children demonstrating features of megaloblastic anemia were scrutinized. Records related to complete blood count (CBC) specially hemoglobin level, MCV, MCH, MCHC, peripheral blood findings, serum folic acid and vitamin B 12 amounts were noted from registers along with the other relevant medical presenting, past and family socioeconomic history. Results: Out of total 294 cases with CBC and peripheral blood findings of macrocytic anemia, 160 were males and 134 found to be females. Mean age was 57 months (4.75 years). Vitamin B12 insufficiency alone was noted in 162 (55.1%) cases, folic acid alone appeared to be deficient in only 8 cases where as combined paucity of both was noticed in 30 cases. Conclusion: Vitamin B12 deficiency found to be the predominant cause of macrocytic anemia in children referred to our institution with 65.3 % of total case population. Considering its significance in the regulation of nervous system, awareness programs with proper guidance are essential to deal this manageable issue.